2015
DOI: 10.1007/s00586-015-4171-z
|View full text |Cite
|
Sign up to set email alerts
|

Hyperexcitability and sensitization of sodium channels of dorsal root ganglion neurons in a rat model of lumber disc herniation

Abstract: These data suggest that NP application produces pain-related behavior and potentiates sodium current density of DRG neurons, which is most likely mediated by enhanced expression of NaV1.7 and NaV1.8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
2
19
0
1
Order By: Relevance
“…Nav1.7 and Nav1.8 expression are also significantly increased in the lumber disc herniation model [52]. Nav1.3 is upregulated in the DRG after nerve injury, in line with the data showing that knockdown of Nav1.3 reduces pain in the neuropathic pain model [53, 54].…”
Section: Mechanism Of Neuropathic Painsupporting
confidence: 58%
“…Nav1.7 and Nav1.8 expression are also significantly increased in the lumber disc herniation model [52]. Nav1.3 is upregulated in the DRG after nerve injury, in line with the data showing that knockdown of Nav1.3 reduces pain in the neuropathic pain model [53, 54].…”
Section: Mechanism Of Neuropathic Painsupporting
confidence: 58%
“…DRG neurons predominantly express Na V 1.7, Na V 1.8 and Na V 1.910. We have previously showed that VGSCs in DRG neurons were sensitized in this setting11. However, the detailed mechanism underlying the sensitization of VGSCs remains unknown.…”
mentioning
confidence: 96%
“…The possible mechanisms included but not excluded the phosphorylation of sodium channels and enhanced trafficking of sodium channels from the cytoplasm to the cell surface membrane. 20 In the present study, although CORT did not alter t in , it significantly reduced Ta of sodium currents. This result suggests that CORT-induced enhancement of sodium current density may not because of aggregation of sodium channel on cell membrane, but at least in part because of changes in channel kinetics.…”
Section: Discussionmentioning
confidence: 59%
“…19 Very recent studies indicated PKC activation leads to an increase in the membrane expression of VGSCs and facilitates sodium currents in cortical neurons, 20,21 indicating that PKC may be involved in mediating VGSCs functions. However, whether and how CORT plays an acute effect on VGSCs of DRG neurons innervating the stomach is not clear.…”
Section: Introductionmentioning
confidence: 99%